Effects of backward-directed resistance on propulsive force generation during split-belt treadmill walking in non-impaired individuals - Moradian, Negar; Ko, Mansoo; Hurt, Christopher P.; Brown, David A. (Frontiers in Human Neuroscience, 2023)
Backward-directed resistance is the resistance applied in the opposite direction of the individual's walking motion. Progressive application of backward-directed resistance during walking at a target speed engages adaptive motor control to maintain that speed. During split-belt walking, a motor control strategy must be applied that allows the person to keep up with the two belts to maintain their position on the treadmill. This situation becomes more challenging when progressive resistance is applied since each limb needs to adapt to the greater resistance to maintain the position. We propose that strategies aimed at changing relative propulsion forces with each limb may explain the motor control strategy used. This study aimed to identify the changes in propulsive force dynamics that allow individuals to maintain their position while walking on an instrumented split-belt treadmill with progressively increasing backward-directed resistance. We utilized an instrumented split-belt treadmill while users had to overcome a set of increasing backward-directed resistance through the center of mass. Eighteen non-impaired participants (mean age = 25.2 +/-2.51) walked against five levels of backward resistance (0%, 5%, 10%, 15%, and 20% of participant's body weight) in two different modalities: single-belt vs. split-belt treadmill. On the single-belt mode, the treadmill's pace was the participant's comfortable walking speed (CWS). In split-belt mode, the dominant limb's belt pace was half of the CWS, and the non-dominant limb's belt speed was at the CWS. We assessed differences between single-belt vs. split-belt conditions in the slope of the linear relationship between change in propulsive impulse relative to change of backward resistance amount. In split-belt conditions, the slower limb showed a significantly steeper increase in propulsion generation compared to the fast limb across resistance levels. As a possible explanation, the slow limb also exhibited a significantly increased slope of the change in trailing limb angle (TLA), which was strongly correlated to the propulsive impulse slope values. We conclude that the motor control strategy used to maintain position on a split-belt treadmill when challenged with backward-directed resistance is to increase the propulsive forces of the slow limb relative to the fast limb by progressively increasing the TLA.ClinicalTrials.gov Identifier: NCT04877249